Reasonableness and risk : right and responsibility in the law of torts - Keating, Gregory C. (New York, NY : Oxford University Press, 2022)
The law of torts is concerned with what we owe to one another in the way of obligations not to interfere with, or impair, each other's urgent interests as we go about our lives in civil society. This book argues that tort law addresses a domain of basic justice and that its rhetoric of reasonableness implies a distinctive morality of mutual right and responsibility.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 2, 2023).
Keywords: Torts; Liability (Law); Communication in law; Law; Laws of specific jurisdictions & specific areas of law